Determination of Some Stand and Site Parameters Influencing the Snow Damage in Trees: A Case Study of Boyabat Forest Enterprise, Turkey - ALTUNEL, Arif Oğuz (Kastamonu University, 2019)
Aim of Study: Determination of the snow damage triggering stand and site parameter on trees.Area of Study: Damaged compartments of Yedicam and Burnuk Forest Directorates, #234 and #116, within Boyabat Forest Enterprise of Kastamonu Regional Directorate of Forestry.Material and Method: Two damaged and two control compartments from each directorate were compared to find if any site or stand parameters are related to the snow damage occurred in the area during 2014-2015 winter. Statistical analysis were carried out to test the significance of the parameters.Main results: Age, relative density, the number of trees, basal area and stand volume of the stand parameters, and slope, site class, terrain roughness and soil depth of the site parameters were statistically linked to the snow damage.Research highlights: The climate is a force to be reckoned with. New strategies must be devised and put into action in forest management. Studies have shown the mishaps. The lessons should be taken from the past experiences. Apparent mistakes must gradually be eliminated.
Keywords: 15. Life on land